Effect of ultrafiltration on whole blood coagulation profile during cardiopulmonary bypass in cardiac surgery: a retrospective analysis - Jaemoon Lee; Dong-Kyu Lee; Won-Kyoung Kwon; Sookyung Lee; Chung-Sik Oh; Klaus Görlinger; Tae-Yop Kim (Korean Journal of Anesthesiology, 2024)
Background Ultrafiltration (UF) would enhance coagulation profiles by concentrating coagulation elements during cardiopulmonary bypass (CPB) for cardiac surgery. Methods We retrospectively reviewed electronic medical records of 75 patients who had undergone cardiac surgery with rotational thromboelastometry-based coagulation management in a university hospital and analyzed the UF-induced changes in the maximum clot firmness (MCF) of extrinsically activated test with tissue factor (EXTEM) during CPB in 30 patients. Results The median volume of filtered-free water was 1,350 ml, and median hematocrit was significantly increased from 22.5% to 25.5%. As the primary measure, UF significantly increased the median MCF-EXTEM from 48.0 mm to 50.5 mm (P = 0.015, effect size r = 0.44). The area under the receiver operating characteristic curve pre-UF MCF-EXTEM for discrimination of any increase of MCF-EXTEM after applying UF was 0.89 (95% CI [0.77, 1.00], P < 0.001), and its cut-off value was 50.5 mm (specificity of 81.8% and sensitivity of 84.2% in Youden’s J statistic). In the secondary analyses using the cut-off value, UF significantly increased the median MCF-EXTEM from 40.5 mm to 42.5 mm in 18 patients with pre-UF MCF-EXTEM ≤ 50.5 mm. However, it did not increase MCF-EXTEM in 12 patients with pre-UF MCF-EXTEM > 50.5 mm. There was a significant interaction between pre-UF MCF-EXTEM values and applying UF (P < 0.001 for the subgroup, P = 0.046 for UF, P = 0.003 for interaction). Conclusions Applying UF improved clot firmness, and the improvement was more pronounced when pre-UF MCF-EXTEM had been reduced during CPB.